Designing a Meta-Synthesis Model of Smartization of the Value Chain with an Industry 4.0 approach - Babaie, Masoud; Erajpour , Alireza; Ehtesham Rasi, Reza (AI and Tech in Behavioral and Social Sciences, 2026)
In the era of the Fourth Industrial Revolution, organizations are compelled to redesign their value chains with a smart and technology-oriented approach. This transformation requires the precise identification of the dimensions and components influencing the smartization of value chains. The aim of this study is to develop a meta-synthesis model that reflects the transformative perspective of smart value chain development in the context of Industry 4.0. The innovation and novelty of the present study lie in its introduction of smart value chain management within the context of the Fourth Industrial Revolution, exploring new and practical models for optimizing supply chain processes and enhancing organizational efficiency. The research is grounded in an interpretivist paradigm and employs the meta-synthesis method to identify a localized framework for value chain smartization. The statistical population consists of academic resources obtained through a systematic search of reputable databases, based on inclusion and exclusion criteria such as relevance, quality, and publication year. All credible scientific documents published between 2018 and 2025 that address the paradigms of smart value chains and the Fourth Industrial Revolution were reviewed. Initially, 153 articles were extracted from reputable databases such as ScienceDirect, Emerald, Sage, Taylor & Francis, and others. After screening titles and abstracts, 38 relevant articles (including 18 literature reviews and 20 empirical studies) were selected and analyzed from the Web of Science database. Structural summaries of these articles led to the identification of broader thematic categories. The findings highlight three key thematic areas linked to smart value chains and Industry 4.0. Through the meta-synthesis approach, eight dimensions and 35 components were extracted: Industry 4.0 technologies, process digitalization, data analytics and intelligent decision-making, value chain integration, resilience and agility, sustainability and social responsibility, organizational empowerment, and business model innovation. The results of this study can provide a strategic roadmap for managers, policymakers, and digital transformation designers across various industries and offer a solid theoretical foundation for future research.